Double-sided glass magnesium rock wool manual purification plate and preparation method thereof

Through the use of modified rock wool and modified hydrophobic coatings, combined with electrostatic spinning technology to prepare heat treatment of nano fiber, the existing double -sided glass magnesium wool handmade purification plate refractory resistance, moisture -proof performance and mechanical performance of poorly achieve. The significant performance of the board improves.

CN119371139AActive Publication Date: 2025-01-28HUAIAN HUAIZHONG CONSTR STEEL PROD TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411497360.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing double-sided glass magnesium rock wool hand-purified plates have poor fire resistance, moisture resistance and mechanical properties.

Method used

Adopt modified rock wool and modified hydrophobic coatings, prepare nano fiber through static spinning technology, and compound it with rock wool substrates and diatom soil to form modifiers with nuclear shell structure Performance and moisture -proof performance.

Benefits of technology

It has significantly improved the mechanical performance, refractory resistance and moisture -proof performance of double -sided glass magnesium wool handmade purification boards, making it more applicable in industries with high precision and high cleanliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005101612480000031
    Figure BDA0005101612480000031
  • Figure BDA0005101612480000051
    Figure BDA0005101612480000051
Patent Text Reader

Abstract

The invention discloses a double-sided glass magnesium rock wool manual purification plate and a preparation method thereof, and belongs to the technical field of preparation of manual purification plates. The double-sided glass magnesium rock wool manual purification plate is prepared from the following components in parts by weight: 20-30 parts of modified rock wool, 30-50 parts of a glass magnesium board, 10-13 parts of an adhesive and 6-9 parts of a modified hydrophobic coating, the hydrophobic agent is prepared from 4, 4 '-diaminodiphenyl ether, pyromellitic dianhydride, zirconium oxychloride octahydrate, a rock wool base material and diatomite, and the modified hydrophobic agent is prepared from octafluoropentanol, isophorone diisocyanate, 3-amino propylene, polyglycol dimethacrylate and acrylic acid. The double-sided glass magnesium rock wool manual purification plate prepared by the method has excellent moisture resistance, fire resistance and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of manual purification board preparation, and specifically relates to a double-sided glass magnesium rock wool manual purification board and a preparation method thereof. Background Art

[0002] With the acceleration of the global industrialization process, especially in the high-precision and high-cleanliness industries such as biopharmaceuticals, medical treatment, food processing, and electronic manufacturing, higher requirements are placed on the cleanliness, safety, and energy efficiency of the production environment. Traditional building materials are often difficult to fully meet these special needs in terms of fire prevention, dust prevention, anti-static, sound insulation, heat insulation, and thermal insulation, which has prompted the development and application of double-sided glass magnesium rock wool manual purification panels.

[0003] The double-sided glass magnesium rock wool manual purification board uses glass magnesium board as the base material. This base material itself has excellent fire resistance, moisture resistance, corrosion resistance and other characteristics, and the production process is environmentally friendly and meets the national green building materials standards. At the same time, the rock wool material filled inside gives the board excellent thermal insulation and good sound absorption, effectively improving the energy efficiency and indoor comfort of the building. Through sophisticated composite technology, the metal outer plate, glass magnesium core material and rock wool layer are closely combined to form a board system with strong integrity and stable structure. This structure not only enhances the mechanical strength of the board, but also significantly improves the fire resistance, dust resistance, anti-static and other properties, enabling it to maintain a stable use state in various harsh environments.

[0004] Patent CN 221067370 U discloses a handmade glass magnesium rock wool purification board, including a shell, the inner side of the shell is provided with reinforcing ribs, the inner side of the reinforcing ribs and the inner side of the insert are provided with multiple groups of glass magnesium boards, the inner sides of the multiple groups of glass magnesium boards are provided with rock wool boards, slots are provided on both sides of the shell, the front and back sides are provided with inserts, and a stopper is provided at one corner of the shell and between the slot and the insert. By directly plugging the insert into the inner side of the slot, the splicing of the shell is more convenient. At the same time, by rotating and flipping the shell, the position of the stopper is always at the diagonal corners of the four shells to avoid gaps in the diagonal corners of the four shells. At the same time, by wrapping the rock wool board with two glass magnesium boards and dispersing the multiple glass magnesium boards on the inner side of the shell through the reinforcing ribs, the fire resistance level of the purification board is improved, the compressive strength is improved, and the surface flatness is improved. However, the fire resistance, moisture resistance and mechanical properties of the purification board prepared by this method still have room for improvement. Summary of the invention

[0005] The object of the present invention is to provide a double-sided glass magnesium rock wool manual purification board and a preparation method thereof, so as to solve the technical problems of poor fire resistance, moisture resistance and mechanical properties of the purification board in the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a double-sided glass magnesium rock wool manual purification board, which is composed of the following components in parts by weight: 20-30 parts of modified rock wool, 30-50 parts of glass magnesium board, 10-13 parts of adhesive, and 6-9 parts of modified hydrophobic coating, wherein the modified rock wool is prepared from 4,4'-diaminodiphenyl ether, pyromellitic acid dianhydride, zirconium oxychloride octahydrate, rock wool substrate and diatomaceous earth, and the modified hydrophobic agent is prepared from octafluoropentanol, isophorone diisocyanate 、 3-aminopropylene, dimethacrylate polyethylene glycol ether and acrylic acid are prepared.

[0008] Preferably, the method for preparing the modified rock wool comprises the following steps:

[0009] Q1: 4,4'-diaminodiphenyl ether is added to a container containing N,N-dimethylformamide for reaction at low temperature, followed by adding pyromellitic anhydride, and stirring thoroughly to obtain a spinning solution, and the spinning solution is prepared into nanofibers using electrospinning technology, and subjected to heat treatment to obtain heat-treated nanofibers;

[0010] Q2: Add zirconium oxychloride octahydrate to distilled water, adjust the pH with ammonia water, heat treat, wash, and vacuum dry to obtain a white powder, ultrasonically disperse the white powder into ethanol, slowly drop silane coupling agent KH-560, ultrasonically disperse, heat to reflux, centrifuge, wash, and dry to obtain a modified powder;

[0011] Q3: Ultrasonic dispersion of the modified powder in ethanol, then addition of heat-treated nanofibers, soaking, washing, drying, and heating treatment to obtain modified nanofibers;

[0012] Q4: The rock wool substrate, modified nanofibers and diatomaceous earth are mixed, cured, cleaned, dried and heat-treated to obtain modified rock wool.

[0013] In the above process, 4,4'-diaminodiphenyl ether and pyromellitic anhydride are first used as raw materials to prepare heat-treated nanofibers, and then zirconium oxychloride octahydrate, ammonia water and silane coupling agent KH-560 are used as raw materials to prepare modified powders. Then, the modified powder nanolayer is in situ grown on the surface of the heat-treated nanofibers by in-situ polar adsorption technology to prepare modified nanofibers with a core-shell structure, and then the rock wool substrate, the modified nanofibers and diatomaceous earth are used as raw materials to prepare modified rock wool, wherein the synthesis reaction formula of the heat-treated nanofibers is as follows:

[0014]

[0015] Preferably, in Q1, the amount ratio of 4,4'-diaminodiphenyl ether, N,N-dimethylformamide and pyromellitic anhydride is (9.25-12.03) g: (130-169) mL: (10.08-13.1) g, the low-temperature reaction temperature is 0-3°C, the reaction time is 2-3h, the sufficient stirring time is 3-5h, and the parameters of the electrospinning technology are: the ambient temperature is 25°C, the ambient humidity is 40%, the spinning voltage is 20-22kV, the syringe propulsion speed is 0.8mL / h, the aluminum foil is used as the receiving substrate and is closely attached to the receiving roller, the distance between the receiving roller and the syringe is 18cm, the roller speed is 450rpm, the spinning time is 10-12h, and the heating treatment process is: from room temperature to 100°C for 0.5h and keep warm for 2h, and then to 300°C for 2h and keep warm for 2h.

[0016] Preferably, in Q2, the dosage ratio of zirconium oxychloride octahydrate and distilled water is (32.25-38.7) g: (1-1.2) L, the pH is adjusted to 9.8-10.2, the heating treatment temperature is 180-200°C, the time is 2-4 h, and after washing with distilled water, it is washed with anhydrous ethanol. The dosage ratio of white powder, ethanol and silane coupling agent KH-560 is (1-3) g: (6-10) mL: (2-4) mL, the ultrasonic dispersion time is 30-45 min, the ultrasonic dispersion time after adding the silane coupling agent KH-560 is 30-60 min, and the reflux time is 5-7 h.

[0017] Preferably, in Q3, the dosage ratio of modified powder, ethanol and heat-treated nanofibers is (1-3) g: (8-12) mL: (2-4) g, the soaking time is 4-7 h, washed with deionized water, the drying time is 20-24 h, and the heating treatment is: from room temperature to 400°C after 2 h and kept warm for 1 h; in Q4, the mass ratio of rock wool substrate, modified nanofibers and diatomaceous earth is (30-50): (3-6): (8-12).

[0018] Preferably, the preparation method of the modified hydrophobic coating comprises the following steps:

[0019] S1: Dissolve octafluoropentanol and isophorone diisocyanate in acetone respectively, then mix and add dibutyltin dilaurate, and then pour into a three-necked flask equipped with a condensing reflux device, a nitrogen protection device and an electric stirrer. After the reaction is complete, cool down, add 3-aminopropylene to continue the reaction, heat to remove acetone, and obtain a fluorine-containing alcohol;

[0020] S2: Heat the dimethacrylate polyethylene glycol ether, then add acrylic acid and 1-butyl-3-methylimidazole tetrafluoroborate into a container, stir until the mixture is uniform, cool, add fluorinated alcohol and 2,2-diethoxyacetophenone, and stir magnetically until the mixture is uniform to obtain a modified hydrophobic coating.

[0021] In the above process, the synthetic reaction formula of the modified hydrophobic coating is as follows:

[0022]

[0023] Preferably, in S1, the molar ratio of octafluoropentanol, isophorone diisocyanate and 3-aminopropylene is (0.9-1.1):(0.8-1.1):(1-1.2), the reaction temperature is 60-80°C, and the reaction time is 3-5h.

[0024] Preferably, in S2, the dosage ratio of dimethacrylate polyethylene glycol ether, acrylic acid, 1-butyl-3-methylimidazole tetrafluoroborate, fluorinated alcohol and 2,2-diethoxyacetophenone is (0.12-0.18) g: (0.3-0.45) mL: (0.23-0.34) mL: (2.23-3.34) g: (0.05-0.075) mL, the heating temperature is 60-70°C, the stirring time is 1-2 h, and the magnetic stirring time is 5-10 min.

[0025] Preferably, the method for preparing the double-sided glass magnesium rock wool manual purification board comprises the following steps:

[0026] Step (1): evenly apply the adhesive on the surface of the modified rock wool and the glass magnesium board, and then combine and compact the two to obtain a double-sided glass magnesium rock wool board;

[0027] Step (2): evenly apply the modified hydrophobic coating on the surface of the double-sided glass magnesium rock wool board, and then put it into a UV box. After polymerization for 2-4 hours, a double-sided glass magnesium rock wool manual purification board is obtained.

[0028] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0029] 1. The present invention first uses 4,4'-diaminodiphenyl ether, pyromellitic acid dianhydride, zirconium oxychloride octahydrate, silane coupling agent KH-560, rock wool substrate and diatomaceous earth as raw materials to prepare modified rock wool, and then uses octafluoropentanol, isophorone diisocyanate, 3-aminopropylene, dimethacrylate polyethylene glycol ether, acrylic acid and 2,2-diethoxyacetophenone as raw materials to prepare a modified hydrophobic coating, and the modified rock wool is placed between glass magnesium plates, and the modified hydrophobic coating is coated on the surface of the glass magnesium plates, which can effectively improve the mechanical properties, fire resistance and moisture resistance of the double-sided glass magnesium rock wool manual purification board.

[0030] 2. The present invention uses 4,4'-diaminodiphenyl ether and pyromellitic anhydride as raw materials to prepare heat-treated nanofibers, and then uses zirconium oxychloride octahydrate and silane coupling agent KH-560 as raw materials to prepare modified powder, and the two are compounded to prepare modified nanofibers. The heat-treated nanofibers have excellent mechanical properties. As a reinforcing phase, they are added to the rock wool substrate to play a skeleton role, which significantly improves the overall mechanical properties of the modified rock wool. The small size and high specific surface area of ​​the heat-treated nanofibers allow them to be evenly distributed in the rock wool substrate, forming an effective stress transfer network, thereby improving the rock wool. Strength and toughness, the modified nanofiber has a core-shell structure, which not only retains the original high-strength characteristics of the nanofiber, but also increases the interfacial bonding force and overall stability of the material, and enhances the mechanical properties of the modified rock wool; the modified powder has excellent fire resistance, which can further protect the rock wool substrate from high temperature damage, and the rock wool substrate and diatomaceous earth have a porous structure. The presence of the pore structure allows it to absorb and store a large amount of heat during the combustion process, reduce the temperature of the material surface, and slow down the combustion rate; at the same time, the presence of the modified powder can also increase the hydrophobicity of the modified rock wool and improve the moisture-proof performance of the manual purification board.

[0031] 3. The present invention uses octafluoropentanol, isophorone diisocyanate, 3-aminopropylene, dimethacrylate polyethylene glycol ether, acrylic acid and 2,2-diethoxyacetophenone as raw materials to prepare a modified hydrophobic coating. Octafluoropentanol is a fluorine-containing alcohol compound, and the fluorine atoms contained in the molecule have extremely strong electronegativity and a small atomic radius, so that the fluorinated segments can be tightly stacked when arranged on the surface of the material to form a barrier layer with low surface energy, thereby making it difficult for water molecules to wetting and spread on the coating surface, giving the coating excellent hydrophobic properties, and the formed cross-linked structure enhances the cohesion and stability of the coating, making the coating denser and tougher, which is conducive to the durability of the hydrophobic property. DETAILED DESCRIPTION

[0032] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1: This example discloses a method for preparing modified rock wool, comprising the following steps:

[0034] Q1: 10.64 g of 4,4'-diaminodiphenyl ether was added to a container containing 149.5 mL of N,N-dimethylformamide, and reacted at 0°C for 2 h. Then, 11.59 g of pyromellitic anhydride was added and stirred for 3 h to obtain a spinning solution. The spinning solution was prepared into nanofibers using electrospinning technology. The parameters of the electrospinning technology were: ambient temperature of 25°C, ambient humidity of 40%, spinning voltage of 20 kV, syringe propulsion speed of 0.8 mL / h, aluminum foil was used as the receiving substrate and attached to the receiving roller, the distance between the receiving roller and the syringe was 18 cm, the roller speed was 450 rpm, the spinning time was 12 h, and the heating treatment process was: heating from room temperature to 100°C for 0.5 h and keeping warm for 2 h, and then heating to 300°C for 2 h and keeping warm for 2 h to obtain heat-treated nanofibers;

[0035] Q2: 35.48g zirconium oxychloride octahydrate was added to 1.1L distilled water, pH was adjusted to 10.2 with ammonia water, heated at 200℃ for 4h, washed with distilled water, washed with anhydrous ethanol, and vacuum dried to obtain white powder. 2g of white powder was ultrasonically dispersed in 8mL ethanol, ultrasonically dispersed for 45min, 3mL silane coupling agent KH-560 was slowly added dropwise, ultrasonically dispersed for 30min, heated under reflux for 5h, centrifuged, washed, and dried to obtain modified powder;

[0036] Q3: 2 g of modified powder was ultrasonically dispersed in 10 mL of ethanol, and then 3 g of heat-treated nanofibers were added, soaked for 6 h, washed with deionized water, dried for 24 h, and heated from room temperature to 400 °C for 2 h and kept for 1 h to obtain modified nanofibers;

[0037] Q4: 40 g of rock wool substrate, 4.5 g of modified nanofiber and 10 g of diatomaceous earth were mixed, cured, cleaned, dried and heat-treated to obtain modified rock wool.

[0038] This embodiment discloses a method for preparing a modified hydrophobic coating, comprising the following steps:

[0039] S1: 1.37 g of octafluoropentanol and 1.19 mL of isophorone diisocyanate were dissolved in 10 mL of acetone respectively, then mixed and 0.03 g of dibutyltin dilaurate was added, and then poured into a three-necked flask equipped with a condensing reflux device, a nitrogen protection device and an electric stirrer, reacted at 70° C. for 3 h, cooled, and 0.49 mL of 3-aminopropylene was added to continue the reaction, and acetone was removed by heating to obtain a fluorine-containing alcohol;

[0040] S2: Heat 0.15 g of dimethacrylate polyethylene glycol ether to 60°C, then add 0.375 mL of acrylic acid and 0.28 mL of 1-butyl-3-methylimidazole tetrafluoroborate into the container, stir for 2 h until the mixture is uniformly mixed, cool, add 2.76 g of fluorinated alcohol and 0.065 mL of 2,2-diethoxyacetophenone, and stir magnetically for 10 min until the mixture is uniformly mixed to obtain a modified hydrophobic coating.

[0041] The present embodiment discloses a double-sided glass magnesium rock wool manual purification board, which is composed of the following ingredients in parts by weight: 25 parts of modified rock wool, 40 parts of glass magnesium board, 11.5 parts of polyurethane adhesive, and 7.5 parts of modified hydrophobic coating.

[0042] This embodiment discloses a method for preparing a double-sided glass magnesium rock wool manual purification board, comprising the following steps:

[0043] Step (1): evenly apply the adhesive on the surface of the modified rock wool and the glass magnesium board, and then combine and compact the two to obtain a double-sided glass magnesium rock wool board;

[0044] Step (2): evenly apply the modified hydrophobic coating on the surface of the double-sided glass magnesium rock wool board, and then put it into a UV box. After polymerization for 2 hours, a double-sided glass magnesium rock wool manual purification board is obtained.

[0045] Example 2: This example discloses a method for preparing modified rock wool, comprising the following steps:

[0046] Q1: 9.25 g of 4,4'-diaminodiphenyl ether was added to a container containing 130 mL of N,N-dimethylformamide, and reacted at 0°C for 2 h. Then, 10.08 g of pyromellitic anhydride was added and stirred for 3 h to obtain a spinning solution. The spinning solution was prepared into nanofibers using electrospinning technology. The parameters of the electrospinning technology were: ambient temperature of 25°C, ambient humidity of 40%, spinning voltage of 20 kV, syringe propulsion speed of 0.8 mL / h, aluminum foil was used as the receiving substrate and attached to the receiving roller, the distance between the receiving roller and the syringe was 18 cm, the roller speed was 450 rpm, the spinning time was 12 h, and the heating treatment process was: heating from room temperature to 100°C for 0.5 h and keeping warm for 2 h, and then heating to 300°C for 2 h and keeping warm for 2 h to obtain heat-treated nanofibers;

[0047] Q2: 32.25 g zirconium oxychloride octahydrate was added to 1 L distilled water, pH was adjusted to 10.2 with ammonia water, and then heated at 200 ° C for 4 h, washed with distilled water, washed with anhydrous ethanol, and vacuum dried to obtain a white powder. 1 g of the white powder was ultrasonically dispersed in 10 mL of ethanol for 45 min, and 4 mL of silane coupling agent KH-560 was slowly added dropwise. After ultrasonic dispersion for 30 min, the mixture was heated under reflux for 5 h, centrifuged, washed, and dried to obtain a modified powder;

[0048] Q3: 1 g of modified powder was ultrasonically dispersed in 12 mL of ethanol, and then 4 g of heat-treated nanofibers were added, soaked for 6 h, washed with deionized water, dried for 24 h, and heated from room temperature to 400 °C for 2 h and kept for 1 h to obtain modified nanofibers;

[0049] Q4: 30 g of rock wool substrate, 6 g of modified nanofiber and 12 g of diatomaceous earth were mixed, cured, cleaned, dried and heat-treated to obtain modified rock wool.

[0050] This embodiment discloses a method for preparing a modified hydrophobic coating, comprising the following steps:

[0051] S1: 1.51 g of octafluoropentanol and 1.38 mL of isophorone diisocyanate were dissolved in 10 mL of acetone respectively, then mixed and 0.03 g of dibutyltin dilaurate was added, and then poured into a three-necked flask equipped with a condensing reflux device, a nitrogen protection device and an electric stirrer, reacted at 70°C for 3 h, cooled, 0.44 mL of 3-aminopropylene was added to continue the reaction, and acetone was removed by heating to obtain a fluorine-containing alcohol;

[0052] S2: Heat 0.18 g of dimethacrylate polyethylene glycol ether to 60°C, then add 0.45 mL of acrylic acid and 0.23 mL of 1-butyl-3-methylimidazole tetrafluoroborate into the container, stir for 2 h until the mixture is uniformly mixed, cool, add 2.23 g of fluorinated alcohol and 0.05 mL of 2,2-diethoxyacetophenone, and stir magnetically for 10 min until the mixture is uniformly mixed to obtain a modified hydrophobic coating.

[0053] The present embodiment discloses a double-sided glass magnesium rock wool manual purification board, which is composed of the following ingredients in parts by weight: 20 parts of modified rock wool, 50 parts of glass magnesium board, 10 parts of polyurethane adhesive, and 9 parts of modified hydrophobic coating.

[0054] This embodiment discloses a method for preparing a double-sided glass magnesium rock wool manual purification board, comprising the following steps:

[0055] Step (1): evenly apply the adhesive on the surface of the modified rock wool and the glass magnesium board, and then combine and compact the two to obtain a double-sided glass magnesium rock wool board;

[0056] Step (2): evenly apply the modified hydrophobic coating on the surface of the double-sided glass magnesium rock wool board, and then put it into a UV box. After polymerization for 2 hours, a double-sided glass magnesium rock wool manual purification board is obtained.

[0057] Example 3: This example discloses a method for preparing modified rock wool, comprising the following steps:

[0058] Q1: 12.03 g of 4,4'-diaminodiphenyl ether was added to a container containing 169 mL of N,N-dimethylformamide, and reacted at 0°C for 2 h. Then, 13.1 g of pyromellitic anhydride was added and stirred for 3 h to obtain a spinning solution. The spinning solution was prepared into nanofibers using electrospinning technology. The parameters of the electrospinning technology were: ambient temperature of 25°C, ambient humidity of 40%, spinning voltage of 20 kV, syringe propulsion speed of 0.8 mL / h, aluminum foil was used as the receiving substrate and attached to the receiving roller, the distance between the receiving roller and the syringe was 18 cm, the roller speed was 450 rpm, the spinning time was 12 h, and the heating treatment process was: heating from room temperature to 100°C for 0.5 h and keeping warm for 2 h, and then heating to 300°C for 2 h and keeping warm for 2 h to obtain heat-treated nanofibers;

[0059] Q2: 38.7 g zirconium oxychloride octahydrate was added to 1.2 L distilled water, pH was adjusted to 10.2 with ammonia water, heated at 200 ° C for 4 h, washed with distilled water, washed with anhydrous ethanol, and vacuum dried to obtain a white powder. 3 g of the white powder was ultrasonically dispersed in 6 mL of ethanol for 45 min, and 2 mL of silane coupling agent KH-560 was slowly added dropwise. After ultrasonic dispersion for 30 min, the mixture was heated under reflux for 5 h, centrifuged, washed, and dried to obtain a modified powder;

[0060] Q3: 3 g of modified powder was ultrasonically dispersed in 8 mL of ethanol, and then 2 g of heat-treated nanofibers were added, soaked for 6 h, washed with deionized water, dried for 24 h, and heated from room temperature to 400 °C for 2 h and kept for 1 h to obtain modified nanofibers;

[0061] Q4: 50 g of rock wool substrate, 3 g of modified nanofiber and 8 g of diatomaceous earth were mixed, cured, cleaned, dried and heat-treated to obtain modified rock wool.

[0062] This embodiment discloses a method for preparing a modified hydrophobic coating, comprising the following steps:

[0063] S1: 1.23 g of octafluoropentanol and 1 mL of isophorone diisocyanate were dissolved in 10 mL of acetone, respectively, and then mixed and 0.03 g of dibutyltin dilaurate was added, and then poured into a three-necked flask equipped with a condensing reflux device, a nitrogen protection device and an electric stirrer. After reacting at 70° C. for 3 h, the temperature was lowered, 0.53 mL of 3-aminopropylene was added to continue the reaction, and the acetone was removed by heating to obtain a fluorinated alcohol;

[0064] S2: Heat 0.12 g of dimethacrylate polyethylene glycol ether to 60°C, then add 0.3 mL of acrylic acid and 0.34 mL of 1-butyl-3-methylimidazole tetrafluoroborate into the container, stir for 2 h until the mixture is uniformly mixed, cool, add 3.34 g of fluorinated alcohol and 0.075 mL of 2,2-diethoxyacetophenone, and stir magnetically for 10 min until the mixture is uniformly mixed to obtain a modified hydrophobic coating.

[0065] The present embodiment discloses a double-sided glass magnesium rock wool manual purification board, which is composed of the following ingredients in parts by weight: 30 parts of modified rock wool, 30 parts of glass magnesium board, 13 parts of polyurethane adhesive, and 6 parts of modified hydrophobic coating.

[0066] This embodiment discloses a method for preparing a double-sided glass magnesium rock wool manual purification board, comprising the following steps:

[0067] Step (1): evenly apply the adhesive on the surface of the modified rock wool and the glass magnesium board, and then combine and compact the two to obtain a double-sided glass magnesium rock wool board;

[0068] Step (2): evenly apply the modified hydrophobic coating on the surface of the double-sided glass magnesium rock wool board, and then put it into a UV box. After polymerization for 2 hours, a double-sided glass magnesium rock wool manual purification board is obtained.

[0069] Example 4: This example discloses a method for preparing modified rock wool, comprising the following steps:

[0070] Q1: 9.95g of 4,4'-diaminodiphenyl ether was added to a container containing 139.8mL of N,N-dimethylformamide, and reacted at 0℃ for 2h. Then, 12.35g of pyromellitic anhydride was added and stirred for 3h to obtain a spinning solution. The spinning solution was prepared into nanofibers using electrospinning technology. The parameters of the electrospinning technology were: ambient temperature of 25℃, ambient humidity of 40%, spinning voltage of 20kV, syringe propulsion speed of 0.8mL / h, aluminum foil was used as the receiving substrate and was closely attached to the receiving roller, the distance between the receiving roller and the syringe was 18cm, the roller speed was 450rpm, the spinning time was 12h, and the heating treatment process was: from room temperature to 100℃ for 0.5h and kept warm for 2h, and then heated to 300℃ for 2h and kept warm for 2h to obtain heat-treated nanofibers;

[0071] Q2: 33.87g zirconium oxychloride octahydrate was added to 1.05L distilled water, pH was adjusted to 10.2 with ammonia water, and then heated at 200°C for 4h, washed with distilled water, washed with anhydrous ethanol, and vacuum dried to obtain a white powder. 1.5g of the white powder was ultrasonically dispersed in 7mL of ethanol for 45min, and 2.5mL of silane coupling agent KH-560 was slowly added dropwise. After ultrasonic dispersion for 30min, the mixture was heated under reflux for 5h, centrifuged, washed, and dried to obtain a modified powder.

[0072] Q3: 1.5 g of modified powder was ultrasonically dispersed in 11 mL of ethanol, and then 2.5 g of heat-treated nanofibers were added, soaked for 6 h, washed with deionized water, dried for 24 h, and heated from room temperature to 400 °C for 2 h and kept for 1 h to obtain modified nanofibers;

[0073] Q4: 35 g of rock wool substrate, 4 g of modified nanofiber and 11 g of diatomaceous earth were mixed, cured, cleaned, dried and heat-treated to obtain modified rock wool.

[0074] This embodiment discloses a method for preparing a modified hydrophobic coating, comprising the following steps:

[0075] S1: 1.44 g of octafluoropentanol and 1.09 mL of isophorone diisocyanate were dissolved in 10 mL of acetone respectively, then mixed and 0.03 g of dibutyltin dilaurate was added, and then poured into a three-necked flask equipped with a condensing reflux device, a nitrogen protection device and an electric stirrer, reacted at 70° C. for 3 h, cooled, 0.47 mL of 3-aminopropylene was added to continue the reaction, and acetone was removed by heating to obtain a fluorine-containing alcohol;

[0076] S2: Heat 0.16 g of dimethacrylate polyethylene glycol ether to 60°C, then add 0.35 mL of acrylic acid and 0.25 mL of 1-butyl-3-methylimidazole tetrafluoroborate into the container, stir for 2 h until the mixture is uniformly mixed, cool, add 2.55 g of fluorinated alcohol and 0.055 mL of 2,2-diethoxyacetophenone, and stir magnetically for 10 min until the mixture is uniformly mixed to obtain a modified hydrophobic coating.

[0077] The present embodiment discloses a double-sided glass magnesium rock wool manual purification board, which is composed of the following components in parts by weight: 22 parts of modified rock wool, 45 parts of glass magnesium board, 12 parts of polyurethane adhesive, and 7 parts of modified hydrophobic coating.

[0078] This embodiment discloses a method for preparing a double-sided glass magnesium rock wool manual purification board, comprising the following steps:

[0079] Step (1): evenly apply the adhesive on the surface of the modified rock wool and the glass magnesium board, and then combine and compact the two to obtain a double-sided glass magnesium rock wool board;

[0080] Step (2): evenly apply the modified hydrophobic coating on the surface of the double-sided glass magnesium rock wool board, and then put it into a UV box. After polymerization for 2 hours, a double-sided glass magnesium rock wool manual purification board is obtained.

[0081] Example 5: This example discloses a method for preparing modified rock wool, comprising the following steps:

[0082] Q1: 11.34 g of 4,4'-diaminodiphenyl ether was added to a container containing 159.3 mL of N,N-dimethylformamide, and reacted at 0°C for 2 h. Then, 10.84 g of pyromellitic anhydride was added and stirred for 3 h to obtain a spinning solution. The spinning solution was prepared into nanofibers using electrospinning technology. The parameters of the electrospinning technology were: ambient temperature of 25°C, ambient humidity of 40%, spinning voltage of 20 kV, syringe propulsion speed of 0.8 mL / h, aluminum foil was used as the receiving substrate and attached to the receiving roller, the distance between the receiving roller and the syringe was 18 cm, the roller speed was 450 rpm, the spinning time was 12 h, and the heating treatment process was: heating from room temperature to 100°C for 0.5 h and keeping warm for 2 h, and then heating to 300°C for 2 h and keeping warm for 2 h to obtain heat-treated nanofibers;

[0083] Q2: 37.09 g zirconium oxychloride octahydrate was added to 1.15 L distilled water, pH was adjusted to 10.2 with ammonia water, heated at 200 ° C for 4 h, washed with distilled water, washed with anhydrous ethanol, and vacuum dried to obtain a white powder. 2.5 g of the white powder was ultrasonically dispersed in 9 mL of ethanol for 45 min, and 3.5 mL of silane coupling agent KH-560 was slowly added dropwise. After ultrasonic dispersion for 30 min, the mixture was heated under reflux for 5 h, centrifuged, washed, and dried to obtain a modified powder;

[0084] Q3: 2.5 g of modified powder was ultrasonically dispersed in 9 mL of ethanol, and then 3.5 g of heat-treated nanofibers were added, soaked for 6 h, washed with deionized water, dried for 24 h, and heated from room temperature to 400 °C for 2 h and kept for 1 h to obtain modified nanofibers;

[0085] Q4: 45 g of rock wool substrate, 5 g of modified nanofiber and 9 g of diatomaceous earth were mixed, cured, cleaned, dried and heat-treated to obtain modified rock wool.

[0086] This embodiment discloses a method for preparing a modified hydrophobic coating, comprising the following steps:

[0087] S1: 1.3 g of octafluoropentanol and 1.28 mL of isophorone diisocyanate were dissolved in 10 mL of acetone respectively, then mixed and 0.03 g of dibutyltin dilaurate was added, and then poured into a three-necked flask equipped with a condensing reflux device, a nitrogen protection device and an electric stirrer, reacted at 70° C. for 3 h, cooled, and 0.51 mL of 3-aminopropylene was added to continue the reaction, and acetone was removed by heating to obtain a fluorine-containing alcohol;

[0088] S2: Heat 0.14 g of dimethacrylate polyethylene glycol ether to 60°C, then add 0.42 mL of acrylic acid and 0.32 mL of 1-butyl-3-methylimidazole tetrafluoroborate into the container, stir for 2 h until the mixture is uniformly mixed, cool, add 3.05 g of fluorinated alcohol and 0.06 mL of 2,2-diethoxyacetophenone, and stir magnetically for 10 min until the mixture is uniformly mixed to obtain a modified hydrophobic coating.

[0089] The present embodiment discloses a double-sided glass magnesium rock wool manual purification board, which is composed of the following components in parts by weight: 28 parts of modified rock wool, 35 parts of glass magnesium board, 11 parts of polyurethane adhesive, and 8 parts of modified hydrophobic coating.

[0090] This embodiment discloses a method for preparing a double-sided glass magnesium rock wool manual purification board, comprising the following steps:

[0091] Step (1): evenly apply the adhesive on the surface of the modified rock wool and the glass magnesium board, and then combine and compact the two to obtain a double-sided glass magnesium rock wool board;

[0092] Step (2): evenly apply the modified hydrophobic coating on the surface of the double-sided glass magnesium rock wool board, and then put it into a UV box. After polymerization for 2 hours, a double-sided glass magnesium rock wool manual purification board is obtained.

[0093] Comparative Example 1: Compared with Example 1, in the process of preparing the modified rock wool in Comparative Example 1, zirconium oxychloride octahydrate is not added, and other conditions remain unchanged.

[0094] Comparative Example 2: Compared with Example 1, in the process of preparing the modified hydrophobic coating in Comparative Example 2, octafluoropentanol was not added, and other conditions remained unchanged.

[0095] Comparative Example 3: Compared with Example 1, in the process of preparing the double-sided glass magnesium rock wool manual purification board in Comparative Example 3, the modified rock wool is replaced by a rock wool substrate, and other conditions remain unchanged.

[0096] Comparative Example 4: Compared with Example 1, in the process of preparing the double-sided glass magnesium rock wool manual purification board in Comparative Example 4, the modified hydrophobic coating is not applied, and other conditions remain unchanged.

[0097] Experimental example: The prepared sample was placed in clean water for immersion for 12 hours, then taken out and the weight of the sample before and after the experiment was measured. 后 -m 前 / m 前 )×100%, the combustion performance of the samples was tested according to GB 8624-2012, and the compressive performance of the samples was tested according to GB / T 50081-2019. The test results are shown in Table 1:

[0098] Table 1

[0099] project Water absorption / % Combustion level Compressive strength / MPa Example 1 1.94 A1 72.8 Example 2 1.98 A1 71.9 Example 3 1.99 A1 71.3 Example 4 1.96 A1 71.6 Example 5 1.97 A1 71.5 Comparative Example 1 2.43 A2 65.4 Comparative Example 2 2.74 A1 71.4 Comparative Example 3 2.57 A2 63.2 Comparative Example 4 2.76 A1 71.3

[0100] It can be seen from the test results in Table 1 that the double-sided glass magnesium rock wool manual purification board prepared in Examples 1-5 of the present invention has excellent moisture resistance, fire resistance and mechanical properties. By comparing Comparative Example 1 with Examples 1-5, it can be seen that the addition of zirconium oxychloride octahydrate can effectively improve the moisture resistance, fire resistance and mechanical properties of the double-sided glass magnesium rock wool manual purification board; by comparing Comparative Example 2 with Examples 1-5, it can be seen that the addition of octafluoropentanol can effectively improve the moisture resistance of the double-sided glass magnesium rock wool manual purification board; by comparing Comparative Example 3 with Examples 1-5, it can be seen that the use of modified rock wool can effectively improve the excellent moisture resistance, fire resistance and mechanical properties of the double-sided glass magnesium rock wool manual purification board; by comparing Comparative Example 4 with Examples 1-5, it can be seen that the application of modified hydrophobic coating can effectively improve the moisture resistance of the double-sided glass magnesium rock wool manual purification board.

[0101] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0102] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. Double-sided glass magnesium rock wool manual purification board, characterized in that: The invention is composed of the following components in parts by weight: 20-30 parts of modified rock wool, 30-50 parts of glass magnesium board, 10-13 parts of adhesive, and 6-9 parts of modified hydrophobic coating, wherein the modified rock wool is prepared from 4,4'-diaminodiphenyl ether, pyromellitic acid dianhydride, zirconium oxychloride octahydrate, rock wool substrate and diatomaceous earth, and the modified hydrophobic agent is prepared from octafluoropentanol, isophorone diisocyanate. 、 3-aminopropylene, dimethacrylate polyethylene glycol ether and acrylic acid are prepared.

2. The double-sided glass magnesium rock wool manual purification board according to claim 1 is characterized in that: The preparation method of the modified rock wool comprises the following steps: Q1: 4,4'-diaminodiphenyl ether is added to a container containing N,N-dimethylformamide for reaction at low temperature, followed by adding pyromellitic anhydride, and stirring thoroughly to obtain a spinning solution, and the spinning solution is prepared into nanofibers using electrospinning technology, and subjected to heat treatment to obtain heat-treated nanofibers; Q2: Add zirconium oxychloride octahydrate to distilled water, adjust the pH with ammonia water, heat treat, wash, and vacuum dry to obtain a white powder, ultrasonically disperse the white powder into ethanol, slowly drop silane coupling agent KH-560, ultrasonically disperse, heat to reflux, centrifuge, wash, and dry to obtain a modified powder; Q3: Ultrasonic dispersion of the modified powder in ethanol, then addition of heat-treated nanofibers, soaking, washing, drying, and heating treatment to obtain modified nanofibers; Q4: The rock wool substrate, modified nanofibers and diatomaceous earth are mixed, cured, cleaned, dried and heat-treated to obtain modified rock wool.

3. The double-sided glass magnesium rock wool manual purification board according to claim 2 is characterized in that: In the Q1, the dosage ratio of 4,4'-diaminodiphenyl ether, N,N-dimethylformamide and pyromellitic anhydride is (9.25-12.03) g: (130-169) mL: (10.08-13.1) g, the low-temperature reaction temperature is 0-3°C, the reaction time is 2-3h, the sufficient stirring time is 3-5h, and the parameters of the electrospinning technology are: the ambient temperature is 25°C, the ambient humidity is 40%, the spinning voltage is 20-22kV, the syringe propulsion speed is 0.8mL / h, the aluminum foil is used as the receiving substrate and is closely attached to the receiving roller, the distance between the receiving roller and the syringe is 18cm, the roller speed is 450rpm, the spinning time is 10-12h, and the heating treatment process is: from room temperature to 100°C for 0.5h and keep warm for 2h, and then to 300°C for 2h and keep warm for 2h.

4. The double-sided glass magnesium rock wool manual purification board according to claim 2 is characterized in that: In the Q2, the dosage ratio of zirconium oxychloride octahydrate and distilled water is (32.25-38.7) g: (1-1.2) L, the pH is adjusted to 9.8-10.2, the heating temperature is 180-200°C, the time is 2-4 h, and after washing with distilled water, it is washed with anhydrous ethanol. The dosage ratio of white powder, ethanol and silane coupling agent KH-560 is (1-3) g: (6-10) mL: (2-4) mL, the ultrasonic dispersion time is 30-45 min, the ultrasonic dispersion time after adding the silane coupling agent KH-560 is 30-60 min, and the reflux time is 5-7 h.

5. The double-sided glass magnesium rock wool manual purification board according to claim 2 is characterized in that: In Q3, the dosage ratio of modified powder, ethanol and heat-treated nanofibers is (1-3) g: (8-12) mL: (2-4) g, the soaking time is 4-7 h, washed with deionized water, the drying time is 20-24 h, and the heating treatment is: from room temperature to 400°C after 2 h and kept warm for 1 h; in Q4, the mass ratio of rock wool substrate, modified nanofibers and diatomaceous earth is (30-50): (3-6): (8-12).

6. The double-sided glass magnesium rock wool manual purification board according to claim 1 is characterized in that: The preparation method of the modified hydrophobic coating comprises the following steps: S1: Dissolve octafluoropentanol and isophorone diisocyanate in acetone respectively, then mix and add dibutyltin dilaurate, and then pour into a three-necked flask equipped with a condensing reflux device, a nitrogen protection device and an electric stirrer. After the reaction is complete, cool down, add 3-aminopropylene to continue the reaction, heat to remove acetone, and obtain a fluorine-containing alcohol; S2: Heat the dimethacrylate polyethylene glycol ether, then add acrylic acid and 1-butyl-3-methylimidazole tetrafluoroborate into a container, stir until the mixture is uniform, cool, add fluorinated alcohol and 2,2-diethoxyacetophenone, and stir magnetically until the mixture is uniform to obtain a modified hydrophobic coating.

7. The double-sided glass magnesium rock wool manual purification board according to claim 6 is characterized in that: In the S1, the molar ratio of octafluoropentanol, isophorone diisocyanate and 3-aminopropylene is (0.9-1.1):(0.8-1.1):(1-1.2), the reaction temperature is 60-80°C, and the reaction time is 3-5h.

8. The double-sided glass magnesium rock wool manual purification board according to claim 6 is characterized in that: In S2, the dosage ratio of dimethacrylate polyethylene glycol ether, acrylic acid, 1-butyl-3-methylimidazole tetrafluoroborate, fluorinated alcohol and 2,2-diethoxyacetophenone is (0.12-0.18) g: (0.3-0.45) mL: (0.23-0.34) mL: (2.23-3.34) g: (0.05-0.075) mL, the heating temperature is 60-70° C., the stirring time is 1-2 h, and the magnetic stirring time is 5-10 min.

9. The method for preparing the double-sided glass magnesium rock wool manual purification board according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step (1): evenly apply the adhesive on the surface of the modified rock wool and the glass magnesium board, and then combine and compact the two to obtain a double-sided glass magnesium rock wool board; Step (2): evenly apply the modified hydrophobic coating on the surface of the double-sided glass magnesium rock wool board, and then put it into a UV box. After polymerization for 2-4 hours, a double-sided glass magnesium rock wool manual purification board is obtained.

Citation Information

Patent Citations

  • Decorative board capable of fire protection and heat insulation

    CN204136516U

  • High-temperature-resistant waterproof environment-friendly composite board

    CN211114391U

  • Magnesium oxide board with high pressure resistance

    CN218489242U

  • Glass magnesium rock wool cleaning board

    CN220848314U

  • Hybrid insulating board for cavity walls

    EP3306002A1